Differences in female labor force participation in East and West Germany: Socialist legacy and pre-socialist tradition - Michael Wyrwich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates the sources of the significantly higher labor force participation of East Ger-man women as compared to their peers in West Germany. The previous literature attributes this to a legacy of socialist labor market policies. This study challenges this hypothesis and demonstrates that the share of women in the labor market across regions that were exposed to the socialist regime was already higher before German division and the introduction of socialist labor market policies. Furthermore, pre-socialist differences and regional conditions play a more important role than socialist legacy in explaining current regional differences in labor force participation of women and in shaping social acceptance of working women. The results suggest that labor market conditions and employment opportunities for women have been more or less not similar before German division. Furthermore, regional differences in current female labor force participation rates seem to be not predominantly shaped by socialist legacy.
Keywords: J16; N34; R23; 330